ANALYSIS OF INNOVATION ACTIVITY IN UZBEKISTAN AND APPROACHES TO MANAGING ENTERPRISE INNOVATION POTENTIAL - Muxamedova , Madinabonu (Educational Research in Universal Sciences, 2023)
Innovation is a crucial element in the growth and development of an economy. Achieving success in innovation activities requires a favorable environment, supportive policies, and efficient management approaches. Uzbekistan has been striving to enhance its innovation capacity and has introduced several measures to promote and support innovation activities. This paper aimed to analyze the innovation activity in Uzbekistan and identify the existing approaches to managing enterprise innovation potential. The study was conducted by reviewing literature, reports, and policies related to innovation and enterprise development in Uzbekistan. The findings suggest that Uzbekistan has a considerable innovation potential, supported by the government’s initiatives and policies. However, there are still several areas that require improvement, such as research and development infrastructure, human capital, and innovation financing. The study also identifies the need for a comprehensive innovation management system at the enterprise level to effectively realize innovation potential. Additionally, the paper recommends the establishment of a national innovation strategy that identifies priority sectors, facilitates collaboration between stakeholders, and provides financial and regulatory support.